SOCIAL MANDATE FOR POLISH LEGISLATIVE AND EXECUTIVE POWER CENTRAL ORGANS IN THE FACE OF CHALLENGES THAT AWAIT THE EU. THE QUESTION OF FOR PUBLIC PARTICIPATION - Potorski, Radosław (The Copernicus Journal of Political Studies, 2018)
Due to amalgamation of Polish and EU systems, the shape of many public policies in the country is the consequence of decisions taken within the EU – but what is more important – with participation of Poles. Complexity of the challenges ahead demands making decisions that the society shall feel are acceptable, or even proceeded with their co-authorship. Relevantly high degree of cooperation, co-decision making and shared responsibility – between executive and legislative power and non-public entities, within political decision making, is important in order to get as properly stable as possible standpoint of Poland, and for efficient implementation. Because of that, the aim of this analysis is the search for the answer to the question whether within challenges that await the EU, we may find those, that will lay especially in the field of interest of Polish non-public entities. In addition – is it justified (and to what extend) to include in such cases those entities into processes of working out standpoints of Polish officials. With such a research objective a thesis is being advanced, that in Poland awareness of EU functioning mechanisms, but also the level of inclusion of non-public entities into political decision making, is little and in face of challenges awaiting the union it is necessary to raise it.